2004
DOI: 10.1007/s10107-004-0554-3
|View full text |Cite
|
Sign up to set email alerts
|

Sparsity in sums of squares of polynomials

Abstract: Abstract.Representation of a given nonnegative multivariate polynomial in terms of a sum of squares of polynomials has become an essential subject in recent developments of sums of squares optimization and SDP (semidefinite programming) relaxation of polynomial optimization problems. We discuss effective methods to obtain a simpler representation of a "sparse" polynomial as a sum of squares of sparse polynomials by eliminating redundancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 16 publications
3
105
0
Order By: Relevance
“…As a by-procut of this result, we prove that a computationally heavy part of EMSSOSP proposed in [3] is redundant for finding a set of unnecessary monomials for an SOS representation of a sparse SOS polynomial. This part enumerates all integer vectors in the convex hull of a set, and the authors in [3] reported that the part has much more computational cost than the other part.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…As a by-procut of this result, we prove that a computationally heavy part of EMSSOSP proposed in [3] is redundant for finding a set of unnecessary monomials for an SOS representation of a sparse SOS polynomial. This part enumerates all integer vectors in the convex hull of a set, and the authors in [3] reported that the part has much more computational cost than the other part.…”
Section: Introductionmentioning
confidence: 71%
“…(2), then stop and return G i . Step 3:: Otherwise set G i+1 = H i and i = i + 1, and go back to Step 2. We remark that EMSSOSP(Ḡ) is EMSSOSP proposed in [3].…”
Section: Algorithm 24 (Emssosp(g))mentioning
confidence: 99%
See 3 more Smart Citations